Heterotrimeric G Protein Alpha Subunit Controls Growth, Stress Response, Extracellular Protease Activity, and Cyclopiazonic Acid Production in Penicillium Camemberti - Levican-Jaque, G; Chavez-Rosales, R; Gil-Duran, C; Rojas-Aedo, J (Elsevier B.V., 2017)
The fungus Penicillium camemberti is widely used in the ripening of various bloomy-rind cheeses. Several properties of P. camemberti are important in cheese ripening, including conidiation, growth and enzyme production, among others. However, the production of mycotoxins such as cyclopiazonic acid during the ripening process by P. camemberti has raised concerns among consumers that demand food with minimal contamination. Here we show that overexpressing an α-subunit from the subgroup I of the heterotrimeric G protein (Gαi) influences several of these processes: it negatively affects growth in a media-dependent manner, triggers conidial germination, reduces the rate of sporulation, affects thermal and osmotic stress resistance, and also extracellular protease and cyclopiazonic acid production. Our results contribute to understanding the biological determinants underlying these biological processes in the economically important fungus P. camemberti. © 2017 British Mycological Society